Study of factors that impact the production of anti-SARS-CoV-2 antibodies in patients with COVID-19: Factors impacting anti-SARS-CoV-2 antibody production - Hussein, Nawfal R; Balatay , Amer; Mohammad , Ameen M; Dhama, Kuldeep; Rasheed, Narin A (Journal of Contemporary Medical Sciences, 2022)
Objectives: The aim of this paper was to investigate the impact of different variables on the production of antibodies in patients who were infected with Covid-19. Methods: This cross-sectional study was conducted in Duhok City, Kurdistan Region of Iraq. The study was conducted between January 2021 and March 2022. Demographic data were collected via face-to-face interview. Antibody levels were determined using Elecsys Anti-SARS-CoV-2. Results: The levels of antibody were studied in 138 patients. A significant association was found between antibody levels and the age of the participants (r=0.175; P=0.04). Besides, a significant correlation was found between antibody levels and the duration of symptoms (r=0.206; P=0.015). The antibody levels were not associated with gender; history of chronic diseases; marital status or time interval before testing. Conclusions: Different variables that may impact the levels of antibody were studied. Significant associations were found between antibody levels and both age and duration of symptoms. Our results can be used by healthcare providers to focus on patients who are at risk of low antibody production.